Influence of Intellectual Capital, Capital Structure, and Corporate Social Responsibility Disclosure on Financial Performance - Keni, Keni Safniati; Fitriati, Azmi; Cinintiya Pratama, Bima; Nur Azizah, Siti (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The purpose of this research is to investigate the influence of intellectual capital, capital structure, and corporate social responsibility disclosure on financial performance. The population of this study consists of mining companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The sampling technique used was purposive sampling, resulting in 166 samples that met the criteria. The data analysis technique employed was multiple linear regression analysis using SPSS software. The research findings indicate that intellectual capital has a positive influence on financial performance, while capital structure and corporate social responsibility disclosure have a negative impact on financial performance. The study concludes on the importance of leveraging intellectual capital, and it highlights the risks of financial failure that companies may face when they use excessive debt and the burden they incur when they disclose too much corporate social responsibility information. The outcomes of this study are anticipated to offer fresh perspectives and insights for companies, the education sector, and relevant stakeholders.